2021
DOI: 10.1596/1813-9450-9551
|View full text |Cite
|
Sign up to set email alerts
|

Taking Stock of Trade Policy Uncertainty: Evidence from China's Pre-WTO Accession

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…Starting in 1986, when China applied to join the international trade arrangement that would become the WTO, this probability began to fall rapidly as trade growth in high-gap industries began to accelerate. By the mid to late 1990s, this probability was only about 5-10 percent, on par with the estimates of Alessandria et al (2019) but lower than the estimates by Handley and Limão (2017). Joining the WTO had a minor effect on the probability of losing access to MFN tariff rates, which is reflected in the trade data: only 10-15 percent of the overall growth in imports of products with a high tariff gap occurred in the 10-year window around WTO accession (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007).…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…Starting in 1986, when China applied to join the international trade arrangement that would become the WTO, this probability began to fall rapidly as trade growth in high-gap industries began to accelerate. By the mid to late 1990s, this probability was only about 5-10 percent, on par with the estimates of Alessandria et al (2019) but lower than the estimates by Handley and Limão (2017). Joining the WTO had a minor effect on the probability of losing access to MFN tariff rates, which is reflected in the trade data: only 10-15 percent of the overall growth in imports of products with a high tariff gap occurred in the 10-year window around WTO accession (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007).…”
Section: Introductionsupporting
confidence: 51%
“…Unlike their work, we estimate a time-varying probability of U.S.-China tariffs over a longer interval. Complementary to our approach, Alessandria et al (2019) estimate a time-varying probability of a change in U.S. trade policy from 1990 to 2005, but use within-year variation in trade flows and trade-policy risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approvals usually occurred in July-September of each year, and several studies noted a relationship between approval timing and trade flows. For instance, Alessandria, Khan, and Khederlarian (2019) found that trade flows increased especially in the months preceding the annual renewal of NTR by the U.S. Congress, that is TPU increased trade. Their empirical model with intrayear variation employed the gap between NTR and non-NTR tariffs, which were as high as 30% for several industries, as the measure of uncertainty.…”
Section: Uncertainty From Binding Overhangmentioning
confidence: 99%
“…The issue of trade policy uncertainty is not new: Episodes of trade disputes among major economies have been well documented, for example Urata (2019) on the US-Japan dispute during the 1980s leading to voluntary export restraints (VER) and import expansion by Japan; Ling, Li, and Swenson (2017) on China's pre-WTO accession and others. Nonetheless, the recent episode takes on significance given the depth of global integration and the uncertainty surrounding these trade restrictions (Handley and Limao 2017;Crowley, Meng, and Song 2018;Alessandria, Khan, and Khederlarian 2019;Steinberg 2019;Amiti, Kong, and Weinstein 2019b;Caldara et al 2020). For instance, figure 1 from the World Trade Organization (WTO) shows the extent of uncertainty in trade policy in the last two years, i.e., a spike in trade restrictive measures imposed by countries and their trade coverage in 2018 and 2019.…”
Section: Introductionmentioning
confidence: 99%